Social capital and the spread of Covid-19: Insights from European countries - Alina K. Bartscher; Sebastian Seitz; Sebastian Siegloch; Michaela Slotwinski; Nils Wehrhöfer (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2020)
We explore the role of social capital in the spread of the recent Covid-19 pandemic in independent analyses for Austria, Germany, Italy, the Netherlands, Sweden, Switzerland and the UK. We exploit within-country variation in social capital and Covid-19 cases to show that high-social-capital areas accumulated between 12% and 32% fewer Covid-19 cases per capita from mid-March until mid-May. Using Italy as a case study, we find that high-social-capital areas exhibit lower excess mortality and a decline in mobility. Our results have important implications for the design of local containment policies in future waves of the pandemic.
Keywords: D04; A13; D91; H11; H12; I10; I18; 330; Covid-19; social capital; collective action; health costs; Europe